Control of communicable diseases manual : an official report of the American Public Health Association - Heymann, David L (American Public Health Association, 2004)
The most widely recognized sourcebook on infectious diseases provides detailed, accurate, informative text for public health workers in official and voluntary health agencies, including those serving in the armed forces and other governmental agencies, and for all students of medicine. Each listing is easy to read and includes identification, infectious agent, occurrence, mode of transmission, incubation period, susceptibility and resistance. The 18th edition of this text is available, for the first time, online. Translations into several languages-currently Spanish, Portuguese, Korean, Serbian, Indonesian and Italian make this text a global treasure.
Keywords: infekční nemoci; kontrola infekčních nemocí; Communicable Diseases; infekční lékařství; Communicable Disease Control; epidemiologie